EDUCATION OF VILLAGE POTENTIAL POST-PANDEMIC IN THE CONTEXT OF COASTAL COMMUNITY ARRANGEMENT IN SURYABAHARI VILLAGE, TANGERANG REGENCY - Fajar Shadiq, Teuku; Prasetyo, Eko; Hasanah, Hani; Syafawi, Lely (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Tangerang Regency spans an area of 377.40 km2 of sea and 298.52 km2 of coastline. The ongoing pandemic has impacted the social systems of villages, particularly in terms of resource governance, including Suryabahari Village in Tangerang Regency. This community service aims to quickly identify the economic potential of coastal communities and raise awareness of the importance of rearranging the village's social system in light of recent changes brought on by the pandemic. The methods employed in this activity include discussions, interviews, and focus group discussions. Discussions were held with the Pakuhaji Sub-District Government and the Suryabahari Village Government to understand the village's potential and challenges. Interviews were conducted with a number of village community leaders to swiftly map the village's potential. Focus group discussions involved representatives from the sub-district government, village government, and the community. The results indicate that a majority of the community demonstrates a high level of resignation towards the changing environment, primarily due to a lack of awareness and available solutions. However, after receiving education, people began to recognize the environmental threats and the need for change.